P1552 Dobutamine stress echocardiography as a screening tool for coronary artery disease detection in patients with end-stage liver disease awaiting transplantation. (17th January 2020) - Masoura, C; Bonou, M; Kapelios, C; Dambasis, D; Skouloudi, M; Barbetseas, J
Abstract: Indroduction: The prevalence of coronary artery disease (CAD) in patients with end-stage liver disease (ESLD) is unknown. However, patients with CAD and ESLD are at increased perioperative risk during liver transplantation. Currently there is no standard protocol for CAD screening in patients with ESLD awaiting orthotopic liver transplantation. We present preliminary data of our experience with dobutamine stress echocardiography in those patients. Methods: Fifty patients (26 males, mean age of 59 years) with end-stage liver disease awaiting transplantation and no history of CAD underwent dobutamine stress echo. The etiology of their hepatic disease was hepatitis B (6 patients), hepatitis C (6 patients), primary billiary cirrhosis (10 patients), sclerosing cholangitis (8 patients), alcoholic hepatitis (10 patients) and polycystic disease (2 patients), while 8 patients had end-stage liver disease of unknown etiology. Twenty-six patients had risk factors for CAD. Eighteen patients had one risk factor and only 8 patients had 2 risk CAD factors. All patients received dobutamine infusion (at escalating doses of 5, 10, 20, 30 and 40 μgr/kg/min), targeting a 85% or more of their age-predicted maximum heart rate. Atropine was administered in 6 patients. Results: All 50 patients had normal inotropic response of left ventricle, without evidence of ischemia (100% studies were negative for ischaemia). No patient had major intolerance to dobutamine. Eight patients experienced hypotension responded to infusion of normal saline. One patient developed paroxysmal supraventricular tachycardia, which was treated with intravenous bolus of adenosine. No patient had cardiovascular events during a follow-up ranging from 1 to 18 months. Twelve patients underwent liver transplantation without any periprocedural cardiovascular events. Conclusions: Dobutamine stress echocardiography is a safe and reliable method for CAD screening in the labile patients with ESLD who are candidates for orthotopic liver transplantation. It seems that the prevalence of significant CAD in this high-risk population is low.